An approach to risk management and preservation of cultural heritage in multi identity and multi managed sites: Al-Haram Al-Ibrahimi/Abraham's Tombs of the Patriarchs in Al-Khalil/Hebron - Alshweiky, Rabab; Unal, Zeynep Gul (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2016)
Al-Khalil, also known as Hebron, is a settlement hosting different belief groups. Al-Haram Al-Ibrahimi or Abraham's Tomb or Tombs of the Patriarchs, names of the same historic sacred site, is the focal point of this settlement. Since this site represents the identity of different belief groups, this condition has indeed initiated conservation problems. In particular, the research puts forward main problems related with the mutually worshipped and used pattern of Al-Haram Al-Ibrahimi/Tombs of the Patriarchs. It further seeks to discuss alternative ways of its structure-oriented conservation. Al-Haram Al-Ibrahimi/Tombs of the Patriarchs is considered to be a holy site located in Al-Khalil/Hebron. Its history dating back to the Middle Bronze Age, Al-Haram Al-Ibrahimi/Tombs of the Patriarchs witnessed Roman, Byzantine, Umayyad, Ayyubid, Mamluk and Ottoman periods, respectively. Above the tombs of Ibrahim/Abraham as well as his prophets and their wives who have religious significance in Islam, Christianity and Judaism; at some point in the Islamic period, a mosque was added and this sacred complex was transformed over time by different civilizations. After the establishment of the Israeli state in 1948, the conditions changed for using Al-Haram Al-Ibrahimi/Tombs of the Patriarchs. Due to the tensions between Israel and Palestine, the building complex, according to the Hebron Protocol, was divided into two to host Jews and Muslims in 1997. This condition created some problems for the sacred site in terms of its sustainable conservation. Since this kind of a division creates difficulties in studying within the section of the other belief group, surveying the building complex as a whole, which is the initial stage of conservation process, is prevented. Thereby, the holistic approach of conservation cannot be applied for this building. Within this context, this research aims to discuss possible solutions for the protection and risk management of Al-Haram Al-Ibrahimi/Tombs of the Patriarchs, as well as evaluate the role of international organization related with heritage conservation. (C) 2016 Elsevier Masson SAS. All rights reserved.
Keywords: Al-Haram Al-Ibrahimi/ Tombs of the; Patriarchs; Risk management; Heritage conservation; Divided heritage sites; Archaeology; Art; Chemistry; Geology; Materials Science; Spectroscopy